Analisis Korelasi antara Penggunaan Sepatu Hak Tinggi dengan Ketidakseimbangan Postur dan Nyeri Pinggang Bawah pada Pekerja Wanita di Perusahaan Retail X Kota Banjarmasin - Juliani Saputri; Akhmad Ridhani; Utomo Wicaksono; Dadan Prayogo; Rizky Ridhayanti; Marvita Marvita (SENTRI: Jurnal Riset Ilmiah, 2025)
High heels have become part of women's professional styles in formal work environments, including the retail industry. However, excessive use of high heels can affect body balance and trigger lower back muscle tension. Biomechanical adaptations due to increased heel height led to changes in pelvic angle, postural deviation, and increased risk of low back pain. The purpose of this study is to analyze the relationship between high heels and postural imbalance and lower back pain levels in female workers in retail companies in Banjarmasin City. The method of this study uses a cross-sectional quantitative design. The sample consisted of 30 female workers aged 20–40 years. The instruments used were the Oswestry Disability Index (ODI) and the Ovako Working Posture Analysing System (OWAS). The data was analyzed using the Spearman Rank Correlation test with a significance level of 0.05. Results: There was a significant relationship between the height of the heel of the shoe and the postural imbalance score (r=0.563; p=0.002) and between postural imbalance and the ODI score (r=0.612; p=0.001). Respondents with >5 cm heel showed the highest risk of lower back pain and postural deviation. The results of the analysis using the Spearman Rank test obtained p-values = 0.001 and rs = 0.612, which shows that there is a significant and strong positive relationship between postural imbalance (OWAS) and lower back pain (ODI) in workers in Retail Company X in 2025.  Conclusion: The use of high heels is significantly associated with postural imbalance and lower back pain. Preventive physiotherapy interventions in the form of core stability exercises, postural re-education, and ergonomics education are needed.